?INFLUENCE OF AQUEOUS LEAF EXTRACT OF .PURPLE NUTS EDGE (CYPERUS ROTUNDUS L.) AND NaCI ON GERMINA- TION AND SEEDLING GROWTH OF WHEAT (TRITICUM AESTIVUM L.) (Biological Sciences - PJSIR, 1999)
Purple nutsedge is one of the ten worst weeds in the world (Holm 1969). Interference by purple nutsedge adversely af- fects the crop yield (William and Warren 1975). Water ex- tract of purple nutsedge tubers inhibited the seed germination of 10 species and inhibition ranged from 0 to 65% and seed- ling growth was also inhibited (Friedman and Horowitz 1971). Aqueous extract of purple nutsedge significantly reduced the germination and seedling growth of tomato, pepper and sor- ghum (Saleem and Fawusi 1983).